The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1142/s0217732307020889
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Holographic Dark Energy Models Using the Differential Ages of Passively Evolving Galaxies

Abstract: Using the absolute ages of passively evolving galaxies observed at different redshifts, one can obtain the differential ages, the derivative of redshift z with respect to the cosmic time t (i.e. dz/dt). Thus, the Hubble parameter H(z) can be measured through the relation H(z) = −(dz/dt)/(1 + z). By comparing the measured Hubble parameter at different redshifts with the theoretical one containing free cosmological parameters, one can constrain current cosmological models. In this paper, we use this method to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…In [572], Yi and Zhang tested the HDE model by using the H(z) data and the LT data. They also verified that the HDE behaves like a quintom-type at 1σ…”
Section: Holographic Dark Energy Modelsmentioning
confidence: 99%
“…In [572], Yi and Zhang tested the HDE model by using the H(z) data and the LT data. They also verified that the HDE behaves like a quintom-type at 1σ…”
Section: Holographic Dark Energy Modelsmentioning
confidence: 99%
“…Here the observed Hubble data H (z i ) and H (z j ) are uncorrelated, for they are obtained by the observations of galaxies at different redshift. Using these nine observational Hubble data one can constrain DE models by minimizing [59][60][61][62][63][64] …”
Section: Constraint On Gcg Model Parametermentioning
confidence: 99%
“…40 These OHD data were also used to constrain the parameters of cosmological models 41,42 and some other relevant works. [43][44][45][46][47] For example, Wei & Zhang(2007a) compared the 9 observational H(z) data with some cosmological models with/without interaction between dark energy and dust matter and found that the OHD data with fairly large errors cannot severely constrain model parameters alone.…”
Section: Introductionmentioning
confidence: 99%